PLATINUM GROUP MINERALS OF THE GAL'MOENAN GABBRO-PYROXENITE-DUNITE MASSIF IN THE SOUTHERN PART OF THE KORYAK HIGHLAND (RUSSIA) - Nazimova Yu.V.; Zaitsev V.P.; Mochalov A.G. (My University, 2003)
The preceding publications (Mochalov et al., 20021,2) were dedicated to a detailed mineralogical characterization of all large, medium, and small placer deposits and collectors in the area of development of the multiphase zonal Gal'moenan and Seinav gabbro-pyroxenite-dunite massifs in the southern part of the Koryak highland. This paper gives characteristics of platinum group minerals (PGM) in rocks of the main bedrock source for placers, the Gal'moenan gabbro-pyroxenite-dunite massif. Platinum group minerals were established in two mineral assemblages: (I) a dispersed PGM assemblage in fine-grained dunites, pyroxenites, and gabbro and (II) an ore PGM assemblage in recrystallized coarse- and giant-grained dunites and in associated chromitites. The article also gives a detailed characterization of the mineral and chemical compositions of these assemblages.